The Bolivia reader : history, culture, politics - Thomson, Sinclair; Barragán R., Rossana (Barragán Romano); Albó, Xavier, 1934-2023; Qayum, Seemin; Goodale, Mark (Latin America readers., 2018)
The Bolivia Reader provides a panoramic view, from antiquity to the present, of the history, culture, and politics of a country known for its ethnic and regional diversity, its rich natural resources and dilemmas of economic development, and its political conflict and creativity. Featuring both classic and little-known texts ranging from fiction, memoir, and poetry to government documents, journalism, and political speeches, the volume challenges stereotypes of Bolivia as a backward nation while offering insights into the country's history of mineral extraction, revolution, labor organizing, indigenous peoples' movements, and much more. Whether documenting Inka rule or Spanish conquest, three centuries at the center of Spanish empire, or the turbulent politics and cultural vibrancy of the national period, these sources--the majority of which appear in English for the first time--foreground the voices of actors from many different walks of life. Unprecedented in scope, The Bolivia Reader illustrates the historical depth and contemporary challenges of Bolivia in all their complexity.